Stratifikasi Sosial dalam Novel La Hami Karya Marah Rusli - Qurratul’ain, Hulwah; Zulfadhli, Zulfadhli (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to describe the social stratification in Sumbawa Island before the eruption of Mount Tambora in 1815 in the novel La Hami by Marah Rusli, which includes; (1) the form of social stratification in the novel La Hami by Marah Rusli (2) the cause of social stratification in the novel La Hami by Marah Rusli, (3) the impact of social stratification in the novel La Hami by Marah Rusli. This research is a literary research using a qualitative approach using a descriptive method whose data are in the form of words, phrases, and sentences, and the data source is taken in the novel La Hami by Marah Rusli. The data collection technique is done by reading and understanding the novel, marking data related to the research problem to gain a deeper understanding of the problem, and inventorizing (searching) the data. The results of this study are that there are three forms of social stratification (layers of society) consisting of a layer of nobles, a layer of people, and a layer of slaves. The noble layer is the highest layer in the life of the people on Sumbawa Island, this noble layer has a high position in the royal government system. The people's layer is the largest layer or called the mass of the people, they are independent but still under the sultanate government. The slave layer is a layer that must work for the royal mangkubumi, they are not free like the masses of the people. Factors causing social stratification in the novel La Hami by Marah Rusli are measures of wealth, measures of power, measures of honor and measures of knowledge. The impacts are social conflict and class endogamy.